The association of smoking with venous thrombosis in women - Blondon, Marc; Wiggins, Kerri L.; McKnight, Barbara; Psaty, Bruce M.; Rice, Kenneth M.; Heckbert, Susan R.; Smith, Nicholas L. (Thrombosis and Haemostasis, 2013)
The evidence for an association between smoking and venous thrombosis (VT) is inconsistent, and its mediation pathways remain to be fully elucidated. A population-based, case-control study was conducted in a large, integrated healthcare system in Washington State, USA. Cases were women aged 18–90 years who experienced a validated incident deep-vein thrombosis or pulmonary embolism between January 1, 1995, and December 31, 2009. Controls were randomly selected from members of the healthcare system. Smoking status (current, former, never) was assessed from medical records review and, for a subset, also by telephone interview. Multivariable logistic regression was used to estimate odds ratios (OR) associated with smoking status. We identified 2,278 cases and 5,927 controls. Subjects comprised mostly postmenopausal white women with a mean age of 66 years and a current smoking prevalence of 10%. Compared to never-smokers, current and former smokers were at higher risk of VT (adjusted OR 1.21, 95% confidence interval [CI] 1.02–1.44 and OR 1.15, 95%CI 1.03–1.29, respectively). These associations were attenuated with further adjustment for potential mediators (cardiovascular disease, congestive heart failure, cancer, recent hospitalisations and physical activity): OR 1.02 (95%CI 0.83–1.25) and 0.95 (95%CI 0.83–1.08), respectively. In conclusion, the modestly increased risk of VT in women who are current or former smokers might be explained by the occurrence of smoking-related diseases and decreased physical activity. Our results do not support a direct biological effect of smoking on the risk of VT that is clinically relevant.Note: Part of this work has been presented as a poster at the 58th annual meeting of the Scientific & Standardization Committee of the ISTH in June 2012.
Keywords: Venous thrombosis; thromboembolism; women; smoking; epidemiology